«¿Será Bolívar un héroe?» - Georges Lomné (Mélanges de la Casa de Velázquez, 2016)
This article seeks to clarify doubts regarding an epithet commonly associated with Simón Bolívar, namely «father of the country» [padre de la patria]. It offers an analysis of the particular context in which it was applied in the time of independence movements, as a means to a clearer understanding of the paradoxes in the heroisation of a figure who came to be worshipped almost as a demi-god throughout a continent. To that end we emphasise the use of this term in New Granada beginning in the 16th century: then, founders of townships and presidents of the Real Audiencia were hailed as new Romuluses until a more Augustan sense of the term came into preferential use in the latter years of the 18th century. During the «New Granada interregnum» (1810-1816), the term retained the ambiguity of the classical tradition, namely the hailing of republican heroes—like Camillus, Fabius, Cincinnatus or the Scipios—and their imperial epigones alike as the first «hero of the century». To distance themselves from the Augustan tradition, associated with the Bourbons, Bolívar and his supporters sought to place the emphasis on another epithet more attuned to the republican essence of their struggle—that is, Liberator, like Brutus the Younger. By 1823 the growing association of the two epithets Liberator and Father of the Country was already raising suspicion of a ravenous appetite for glory in their bearers. As a result, Andrés Bello sought to downplay Bolívar’s reputation from London, above all others the source-point of its fabrication: and so he acclaimed other Venezuelan and New Granadan heroes before taking exile in Chile in 1829, where he stood up as the herald of domestic heroism, the only kind attuned to Freedom in the minds of Modernists.